Substrate polyspecificity and conformational relevance in ABC transporters: new insights from structural studies. (4th December 2018) - Wright, Jack; Muench, Stephen P.; Goldman, Adrian; Baker, Alison
Abstract : Transport of molecules and ions across biological membranes is an essential process in all organisms. It is carried out by a range of evolutionarily conserved primary and secondary transporters. A significant portion of the primary transporters belong to the ATP-binding cassette (ABC) superfamily, which utilise the free-energy from ATP hydrolysis to shuttle many different substrates across various biological membranes, and consequently, are involved in both normal and abnormal physiology. In humans, ABC transporter-associated pathologies are perhaps best exemplified by multidrug-resistance transporters that efflux many xenobiotic compounds due to their remarkable substrate polyspecificity. Accordingly, understanding the transport mechanism(s) is of great significance, and indeed, much progress has been made in recent years, particularly from structural studies on ABC exporters. Consequently, the general mechanism of 'alternate access' has been modified to describe individual transporter nuances, though some aspects of the transport process remain unclear. Moreover, as new information has emerged, the physiological relevance of the 'open-apo' conformation of MsbA (a bacterial exporter) has been questioned and, by extension, its contribution to mechanistic models. We present here a comprehensive overview of the most recently solved structures of ABC exporters, focusing on new insights regarding the nature of substrate polyspecificity and the physiological relevance of the 'open-apo' conformation. This review evaluates the claim that the latter may be an artefact of detergent solubilisation, and we hypothesise that the biophysical properties of the membrane play a key role in the function of ABC exporters allowing them to behave like a 'spring-hinge' during their transport cycle.